Design of Internal Quality Assurance System (SPMI) in Facing Accreditation of Islamic Values-Based Educational Institutions at Madrasah Diniyah Takmiliyah (MDT) Insan Cita Tanjung Pinang. - Ria Kurniawaty; Ricka Sofiana (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
Educational institutions can become quality educational institutions if they have a quality culture. One effort to build a quality culture of educational institutions is to implement the Internal Quality Assurance System (SPMI). The focus of this study is the Implementation of the Internal Quality Assurance System (SPMI) at Madrasah Diniyah Takmiliyah Insan Cita. The formulation of the problem in this study is how the implementation of SPMI (Internal Quality Assurance System) at MDT Insan Cita Tanjung Pinang, and how it impacts educational services at the madrasah. The purpose of this study is to analyze how the implementation of the Internal Quality Assurance System (SPMI) and its impact on improving the quality of education at MDT Insan Cita Tanjung Pinang. Data were obtained through observation, interviews, and documentation. Based on the results of the study by analyzing the implementation of SPMI at MDT Insan Cita in terms of input, process, output, outcome and impact, we can obtain in-depth insights into the successes, challenges, and potential improvements in efforts to improve the quality of education at the madrasah.